Experimental Research on Physical Indices and Mechanical Properties of Sandstone under Combined Action of Chemical-Freeze-Thaw Cycles. Issue 1 (February 2020) - Feng, Xuezhi; Wang, Yongyan; Ge, Qiang; Yu, Zhuoqun
Abstract: In order to study the effects of chemical solution erosion and freeze-thaw cycles on the physical parameters and mechanical properties of rocks, sandstone samples from central Shandong Province were taken as the research objects. The freeze-thaw cycle test and uniaxial compression test were carried out for rock samples eroded by 0.01mol/L H2SO4 solution, 0.01mol/L NaCl solution and 0.01mol/L NaOH solution, respectively. The results show that the mass loss and porosity of rock samples eroded by different chemical solutions increase with the increase of freeze-thaw cycles, and the peak strength and elastic modulus decrease exponentially with the increase of freeze-thaw cycles. The damage degree of acidic solution to freeze-thaw cycling sandstone samples is the greatest, that of alkaline solution is the next, and that of neutral solution is the smallest. The conclusions can be used for reference in support and design of underground engineering.